Rational Design Strategy for Triboelectric Nanogenerators Based on Electron Back Flow and Ionic Defects: The Case of Polytetrafluoroethylene - Fatti, Giulio; Ciniero, Alessandra; Ko, Hyunseok; Lee, Han Uk; Na, Yujin; Jeong, Chang Kyu; Lee, Sang Geul; Kwak, Dongyub; Park, Kwi Il; Cho, Sung Beom; Dini, Daniele (Advanced Electronic Materials, 2023)
The lack of theoretical understanding of triboelectrification has hindered the development of energy harvesting technologies like triboelectric nanogenerators. Focusing on polytetrafluoroethylene, a material with a strong triboelectric output, a model predictive of its triboelectric behavior, driving the development of improved nanogenerators are formulated. With a combined computational-experimental approach it is shown that defluorination enhances polytetrafluoroethylene nanoscale triboelectric charging. Then a model, explaining the macroscale triboelectric output as determined by the competition of two mechanisms is developed. Defluorination enhances charging while also reducing the interface gap, favoring the backflow of electrons, and possibly reducing charging. However, numerical analysis shows that backflow is negligible, aligning with the prediction of increased triboelectric output. By building triboelectric nanogenerators with defluorinated polytetrafluoroethylene samples, achieved by X-ray irradiation, a one-order-of-magnitude output increase is demonstrated. The predictive models, supported by experiments, lead to an improved strategy for designing effective energy harvesting devices and new applicative breakthroughs.
Keywords: Back flow; Defluorination; Design strategies; DFT calculation; Ionic defects; Model predictive; Nanogenerators; Rational design; Triboelectric nanogenerator; Triboelectrification; DFT calculations; energy harvesting; polytetrafluoroethylene; triboelectric nanogenerators; triboelectrification